A Review of Labor Law in Addressing the Threats of Termination of Employment Relations in the Era of Artificial Intelligence Technology Disruption - Evaline Suhunan Purba; Wilma Silalahi (Dinasti Research, 2024)
Artificial Intelligence is a concept related to the development of technology in the 4.0 era and society 5.0. The presence of Artificial Intelligence in people's lives provides significant changes to people's lives. The use of artificial intelligence is so popular that it has been widely used by all circles of society. The presence of artificial intelligence is considered to provide many benefits to society, but the existence of artificial intelligence also brings changes in the field of labor because it causes a reduction in labor in various fields. With the reduction of workers, it will increase the number of unemployed. This research suggests that labor law must provide protection for workers' rights in the current digital era.